Anticancer And Anti-inflammatory Activities Of Girinimbine Isolated From Murraya Koenigii - Venoos Iman; Syam Mohan; Siddig Ibrahim Abdelwahab; Hamed Karimian; Noraziah Nordin; Mehran Fadaeinasab; Mohamad Ibrahim Noordin; Suzita Mohd Noor (Dovepress, 2024)
Indexed by Scopus